Creative Communication Strategy for Digital Marketing and E-Commerce in Product Sales (Case Study, Shopee, Tokopedia, Tiktok Shop) - Uva, Iva Mas; Eva Ariati; M.Ruslan Amiruddin; Dicka Tegarisnandy; Wulan Furie (PT FORMOSA CENDEKIA GLOBAL, 2024)
The development of the internet has penetrated all sectors, one of which is the online sales system or what is often called e-commerce. Shopee, Tokopedia and Tiktok shop are one of the most widely used e-commerce applications in Indonesia. The aim of this research is to see the influence of commerce applications. Shopee, Tokopedia and Tiktok shop for promotional media to increase product selling power in terms of sellers. The research method is descriptive qualitative by collecting research data through interviews and observing research objects. Based on the results obtained, it is clear that Shopee, Tokopedia and Tiktok shop can be used as promotional media to increase the selling power of products as social marketing contacts. This is because the features of Shopee, Tokopedia and Tiktok shop make it very easy for sellers to carry out promotions so that product sales are higher. However, you need to realize that e-commerce applications will continue to develop along with the needs of buyers and sellers, so Shopee, Tokopedia and Tiktok shop need to make various improvements so that they can always be used as social marketing contacts